Hubungan Teknik Pernafasan dengan Kemajuan Persalinan - Ika Putri Damayanti (STIKes Hang Tuah Pekanbaru, 2015)
Breathing techniques is a technique that can be useful to overcome the pain of childbirth. So that, mother was not overwhelmed when having contractions, besides that technical breathing also help the process of childbirth to run normally. Based on preliminary studies on BPM Deliana S. of 218 peoples be found 16 peoples (18%) maternal have difficulty in breathing techniques set properly when straining causing the second time is obstructed. The purpose of this research is to know the corelations between breathing technique with the progress of childbirth. The kind of research is all of maternal in 2015, with a maternal sampling from January to March 2015 that amount 63 peoples. And using bivariate analysis by using chi square test. Results of this research is that of the 39 respondents who uses correct breathing techniques majority of the progress of labor by 32 respondents (82.1%), with a p-value of 0.004 (p <0.05), means that there is a relationship between breathing techniques with progress childbirth. The conclusion is any correlation between breathing techniques with the progress of childbirth, so that the breathing techniques was important to applied in the childbirth process to be able to help the process of childirth.